Chronic overheating in low carbon urban developments in a temperate climate. (July 2017) - McLeod, Robert S.; Swainson, Michael
Abstract: Numerous studies have reported on overheating in urban contexts the majority of which have focused on the influences of external factors, such as: heat waves and climatic change. To date very little research has examined the more insidious issue of chronic year-round overheating in temperate climatic zones. The present study begins by reviewing the potential implications of planning and legislative constraints underlying urban residential design. A case study example is then introduced to examine the potential manifestation of such issues in practice. Detailed field monitoring and survey data from a number of newly built flats in a multi-residential block in London, is presented. Typical of a new generation of urban dwellings the development incorporates a high thermal specification together with low carbon building services, such as communal heating systems and mechanical ventilation with heat recovery. Through detailed zonal measurements of a broad range of environmental and building services parameters it has been possible to isolate the key factors underpinning poor overheating performance for these flats. The findings of this case study are part of a larger research project investigating the causes of overheating in high density urban dwellings across Greater London. The results suggest that the causes of chronic overheating in these modern low-energy flats are multiple, but typically share common factors stemming from poorly integrated architectural and MEP design decisions. Conflicts between regional planning policies, UK building regulations, and health and safety legislation appear to be compounding the problem.